Length-Dependent Structural Transformations of Huntingtin PolyQ Domain Upon Binding to 2D-Nanomaterials - Feng, Mei; Bell, David R.; Wang, Zhenhua; Zhang, Wei (Frontiers in Chemistry, 2020)
There is a strong negative correlation between the polyglutamine (polyQ) domain length (Q-length) in the intrinsically disordered Huntingtin protein (Htt) exon-1 and the age of onset of Huntington’s disease (HD). PolyQ of Q-length longer than 40 has the propensity of forming very compact aggregate structures, leading to HD at full penetrance. Recent advances in nanobiotechnology has provided a new platform for the development of novel diagnosis and therapeutics. Here, we explore the possibility of utilizing 2D-nanomaterials to inhibit the formation of supercompact polyQ structures through the so-called “folding-upon-binding” where the protein structure is dependent on the binding substrate. Using molecular dynamics simulations, we characterize two polyQ peptides with Q-length of 22 (Q22, normal length) and 46 (Q46, typical length causing HD) binding to both graphene and molybdenum disulfide (MoS2) nanosheets, which have been applied as antibacterial or anticancer agents. Upon binding, Q22 unfolds and elongates on both grapheme and MoS2 surfaces, regardless of its initial conformation, with graphene showing slightly stronger effect. In contrast, initially collapsed Q46 remains mostly collapsed within our simulation time on both nanosheets even though they do provide some “stretching” to Q46 as well. Further analyses indicate that the hydrophobic nature of graphene/MoS2 promotes the stretching of polyQ on nanosheets. However, there is strong competition with the intra-polyQ interactions (mainly internal hydrogen bonds) leading to the disparate folding/binding behaviors of Q22 and Q46. Our results present distinct Q-length specific behavior of the polyQ domain upon binding to two types of 2D-nanomaterials which holds clinical relevance for Huntington's disease.